Production technology and fruit tree nutrition - Gonda, I. (International Journal of Horticultural Science, 2003)
Fruit yield quality and quantity are effectively enhanced if healthy vegetative conditions are ensured. These optimal conditions — i.e. the balance between shoot development and yield — can be achieved by the rationalization of the production technologies, such as: • reduction of the size of the crown • adaptation of the severity and method of pruning to the conditions of the actual year • removal of the shoot tips • timely fruit thinning By establishing an improved level of plant nutrient uptake, this will ensure a healthy balance between shoot growth and yield.